Correlative metabolomic fingerprinting and molecular docking studies of dermatological phytotherapeutics of South-Eastern Himalaya - Priyankar Dey; Indrani Sarkar; Somit Dutta; Manas Ranjan Saha; Tapas Kumar Chaudhuri (Journal of Traditional and Complementary Medicine, 2019)
Viburnum erubescens Wall., Rhododendron arboretum Sm., Eurya japonica Thumb., Symplocos lucida (Thunb.) Siebold & Zucc, and Symplocos pyrifolia Wall. ex G. Don are extensively used by the native and ethnic populations of the South-Eastern Himalayan region for several dermatological conditions, yet their phytochemical composition remained largely unknown. Therefore, the aim of the study was to explore the therapeutically relevant volatile phytochemical compositions and study the molecular interactions against intracellular cytoregulatory transcription factors. Leaves of the five plants were subjected to Gas chromatography-Mass spectrometry (GCMS) post silylation derivation. The results were further analyzed using multivariate statistical methods such as Principal Component Analysis (PCA) and Hierarchical Cluster Analysis (HCA). A total of 115 compounds were identified in the five plants. Multivariate analysis revealed optimum metabolomic correlation between S. pyrifolia and S. lucida (0.876), whereas lowest correlation was found between E. japonica and V. erubescens (−0.242). Arbutin, β-amyrin, betulin, β-sitosterol and stigmasterol demonstrated highest interaction with the molecular targets. Collectively, the present study revealed the bioactive volatile phytochemicals responsible the therapeutic uses against diverse skin conditions. Keywords: Gas chromatography-Mass spectrometry, Molecular docking, Multivariate statistics, Silylation, Volatiles